O emprego das formas dativas de segunda pessoa na escrita do nordeste brasileiro do século XX: uma mudança em curso - Silva, Franklin Costa da (2017)
In the present research, we analyze the use of dative forms in a second person context (singular and plural) in private letters of Brazilian Portuguese (hereinafter PB), from three different Northeastern states, namely Rio Grande do Norte (RN), Pernambuco (PE) and Bahia (BA); correspondences written in the 20th century. Our corpus consists of copies shared in the site of the common minimum printed corpus of the Project for the History of Brazilian Portuguese (PHPB). Two theoretical and methodological perspectives supported our work: The Theory of Variation and Change (TVM) (see WEINREICH, LABOV, HERZOG, 2012 [1968], hereinafter WLH, LABOV, 2008 [1972]) and the Theory of Principles and Parameters (P&P), Chomsky, 1995). This way, we conduct a qualitative and quantitative analysis, willing to map and explain the following linguistic variable: the second person singular and plural dative forms (P2 and P5) in Brazilian Portuguese. As well as its competing linguistic variants: different possibilities of realization that compete for P2 and P5, like the pronominal te / ti, vos / vós, of the ellipse (ᴓ), in addition to the pronouns você, vocês and tu preceded by the prepositions a / para / prá / de / em. Among the other objectives that guide our research, we highlight the following: to investigate whether the grammatical relation of OI (indirect complement (CI) - "true indirect object") or oblique complement (CO) restricts or favors, respectively, the implementation of competing linguistic variants of the dative pronouns. We hypothesized that the competing variant forms would not be influenced by the grammatical relationship of OI or OBL (CO). However, these grammatical relationships proved to be one of the most important conditioners of the variation amongst the competing forms. After identifying and characterizing the 610 data present within the letters, we submitted them to rounds in the GoldVarb program, electing 10 (ten) independent variables; social and linguistic ones, which referred us to some variable rules. In general, data analysis points to a change in progress in favor of the competing forms of the prepositioned você-tu paradigm, passing first by competitors lhe and the ellipse (ᴓ), leaving the standard variants of the standard Te / Ti restricted to specific contexts, such as communications involving more affectivity, more informality.